On how students of the first year at the Foreign Languages Department chose which major to study at the University of El Salvador - Mejía, Estela Marisol
This study delves deeply into the decisions made by students when choosing to study a major in English language teaching and explores the reasoning behind them. We answer how students resolved to study this major, and what kind of information they received in order to understand how educated, suitable and informed their decision may have been. By any definition, professional success is what most students aspire upon enrolling to pursue a degree in university. Needless to say, students may experience various difficulties throughout their journey towards completing their studies in a major. Most students would often struggle to identify the relevant factors that may prevent them from performing as required. Some students may develop poorly due to various elements related specifically to the demands and characteristics of the major they chose (Cupani et al, 2004). In this sort of instances is when fields such as career election may prove to be a wider and more thorough process than most students seem to perceive when making the decision to enroll to a major.There are specific fields of research endeavored to understand why students choose a major and in turn help them identify which major may be more suitable or adequate for them. Areas such as that of career choice and students’ early development are sometimes overlooked due to a wide array of aspects. These aspects can go from simply to not being aware. Even though most students seem to be somewhat cautious when it comes to choosing a major, we need to realize that most of the process derives from the student’s perception of not only the major and its curriculum but also the implications that both may have towards his or her personal aspirations.